Risk of complications in the late vs early days of the 42nd week of pregnancy: A nationwide cohort study. (6th December 2021) - Andersson, Charlotte Brix; Petersen, Jesper Padkaer; Johnsen, Søren Paaske; Jensen, Martin; Kesmodel, Ulrik Schiøler
Abstract: Introduction: Uncertainty remains about the most appropriate timing of induction of labor in late‐term pregnancies. To address this issue, this study aimed to compare the risk of neonatal morbidity and pregnancy‐ and birth‐related complications between gestational age (GA) 41 +4 –42 +0 and GA 41 +0 –41 +3  weeks. Material and methods: This nationwide registry‐based cohort study included singleton births without major congenital malformations, with registered GA, and with intended vaginal delivery at GA 41 +0 – 42 +0  weeks between 2009 and 2018 in Denmark. Logistic regression models were used to estimate the crude risk ratio and adjusted risk ratio (RRA ) of neonatal and obstetric adverse outcomes in births at GA 41 +4 – 42 +0  weeks compared with GA 41 +0 – 41 +3  weeks. The results were adjusted for relevant confounders, including induction of labor. Results: A higher incidence of neonatal morbidity and birth complications was observed in births at GA 41 +4 –42 +0  weeks than in births at GA 41 +0 –41 +3  weeks. Neonatal morbidities included an increased risk of low Apgar score (Apgar 0–6 after 5 min; RRA 1.17, 95% confidence interval [CI] 1.01–1.34), meconium aspiration (RRA 1.25, 95% CI 1.06–1.48), need for respiratory support (continuous positive airway pressure; RRA 1.09, 95% CI 1.03–1.15), and a composite outcome of need for comprehensive treatment at a neonatal department or neonatal death (RRA 1.65, 95% CI 1.29–2.11). Birth complications included emergency cesarean section (RRA 1.17, 95% CI 1.14–1.21), severe lacerations (RRA 1.11, 95% Cl 1.04–1.17), and increased blood loss after birth (RRA 1.13, 95% CI 1.06–1.21). Conclusions: Births at GA 41 +4 –42 +0  weeks were associated with an increased risk of neonatal morbidity and birth complications compared with births at GA 41 +0 –41 +3  weeks. The results of this study may aid clinicians in deciding when to recommend induction of labor in late‐term pregnancies.